Cytophysiological manifestations of wheat’s defense reactions against stem rust induced by the biofungicide Novochizol - A. B. Shcherban; L. Ya. Plotnikova; V. V. Knaub; E. S. Skolotneva; V. V. Fomenko (Вавиловский журнал генетики и селекции)
Biologization is a priority direction of agricultural production. One of the promising approaches to solve the biologization problem is the use of chitosan-based biopreparations to stimulate plant growth and protect plants from a wide range of pathogens. Currently, active work is underway to create and test new chitosan preparations. Novochizol was obtained as a result of intramolecular crosslinking of linear chitosan molecules and has a globular shape. Previously, a Novochizol-stimulating effect on the growth and development of common wheat was demonstrated. However, the induced resistance mechanisms against rust diseases have not been studied before. The reported studies have revealed the dose effect of the preparation on the development of wheat stem rust. The best results of visual estimation of plant reactions were obtained with 0.125 and 0.75 % Novochizol pretreatment four days before rust infection. After pretreatment of susceptible cv. Novosibirsk 29 seedlings, a resistant reaction appeared and the urediniopustule density was decreased. Cytophysiological studies have shown that 0.75 % Novochizol stimulated an intensive accumulation of hydrogen peroxide H2O2 in the leaves of the infected and healthy plants within 48 hours post inoculation (h p/in). During the period of 48–144 h p/in, H2O2 gradually disappeared from tissues, but its content increased significantly at the sporulation stage around pustules. However, Novochizol did not induce the hypersensitivity reaction in infected plants. The preparation induced an earlier and more intensive (compared with untreated plants) accumulation of phenolic substances with different autofluorescence in the zones around pathogen colonies. Novochizol induced a change in the ratio of phenols with different spectral characteristics towards compounds with an increased content of syringin derivatives. This work is the first stage in the study of Novochizol effects on wheat defense mechanisms against stem rust. The research will be continued using molecular genetics, biochemical and cytophysiological methods.